WIND ENERGY - ORIPOVA DILNOZA KARIMJON KIZI; YUSUPOV ABDURASHID KHAMIDILLAEVICH (TADQIQOTLAR, 2025)
Annotation: This scientific work discusses the natural source of wind energy, its  operating  principles,  advantages,  and  disadvantages.  The  study  highlights  the technology  of  generating  electricity  through  wind  turbines,  their  environmental cleanliness, and economic efficiency. It also analyzes the potential and prospects for the  development  of  wind  energy  in  the  context  of  Uzbekistan.  Furthermore,  the necessity of transitioning to renewable energy sources and the role of wind energy in sustainable development are emphasized.